The Effectiveness of Foresight and Systemic Thinking of Strategic Intelligence to Improving the Tourism Organization Superiority - Semir khelil Ibrahim Shamto; Dr. Amel Chaabouni (Kurdish Studies, 2024)
The Foresight and systems thinking represent a systematic method to employ the development ideas of the tourism organization, as these two elements enable better preparation for the expected change in the business environment; This allows the organization to face challenges and invest in opportunities that enable it to make appropriate decisions to excel. The research aims to study the effectiveness of foresight and systems thinking in improving the superiority of the tourism organization.